Conceptualization of Man’s Behavioral and Physical Characteristics as Animal Metaphors in the Spoken Discourse of Khezel People - Aliakbari, Mohammad; Faraji, Elham (Linguistik Online, 2014)
Cognitive theory of metaphor has changed our understanding of metaphor as a figurative device to a matter of thought. It holds that metaphors are cognitively as well as culturally motivated. Despite having similar images in some languages, the culture-specific aspect of animal metaphors inspired the researchers to explore this area of metaphoric system in a local Kurdish variety to investigate how animal metaphors are reflected in spoken discourse. To achieve this objective, the authors collected and analyzed animal expressions adopted for praise and degradation of physical and behavioral characteristics in Khezeli dialect in Ilam, Iran. To create a representative corpus, the authors scrutinized spoken language and oral poetry of the dialect. The collected data indicate that more wild than domestic and more degrading than praising animal expressions are used for man’s physical and behavioral characteristics. It is also confirmed that aspects of appearance, size, physical characteristics as well as body parts of animals are transferred to humans. Further, users’ attitudes toward animals reflected themselves in their metaphors. Users were also found to have three categories of positive, positive/negative, and negative connotations for animal names. Despite the existence of similarities in the underlying patterns of metaphoric use in different languages, the research came to the conclusion that the types of animals used, their connotations and interpretations may be worlds apart and taking the meaning of one for another may lead to misunderstanding.